The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1161/circulationaha.108.817247
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Embolization of an Inferior Vena Cava Filter Strut Leading to Cardiac Tamponade

Abstract: A 56-year-old woman presented to the Emergency Department of Parkland Memorial Hospital complaining of chest pain. She had a remote history of a hemorrhagic cerebrovascular accident complicated by pulmonary embolism, for which a Gunther-Tulip inferior vena cava (IVC) filter had been placed 6 years previously. In the triage area, the patient collapsed and was found to be hypotensive. An ECG showed sinus bradycardia with nonspecific ST and T-wave changes ( Figure 1). Bedside echocardiography demonstrated a moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…En otra serie de 400 pacientes la trombosis de VCI se observ贸 en 4,7% de ellos 12 . Otra de las complicaciones que pueden ocurrir es la migraci贸n del filtro y oclusi贸n del ostium de alguna rama venosa con obstrucci贸n de la misma, lo que no ocurri贸 en nuestro paciente 19 . Este paciente present贸 una trombosis aguda de la VCI, bajo un filtro instalado en una posici贸n superior a los ri帽ones, con extensi贸n de la trom-bosis a ambas venas renales.…”
Section: Discussionunclassified
“…En otra serie de 400 pacientes la trombosis de VCI se observ贸 en 4,7% de ellos 12 . Otra de las complicaciones que pueden ocurrir es la migraci贸n del filtro y oclusi贸n del ostium de alguna rama venosa con obstrucci贸n de la misma, lo que no ocurri贸 en nuestro paciente 19 . Este paciente present贸 una trombosis aguda de la VCI, bajo un filtro instalado en una posici贸n superior a los ri帽ones, con extensi贸n de la trom-bosis a ambas venas renales.…”
Section: Discussionunclassified
“…There is a paucity of studies addressing the optimal management of patients with migrating struts from fractured IVC filters. A review of the literature revealed only eight case reports [2][3][4][5][6][7][8][9] clearly documenting IVC filter fragment migration to the right ventricle. A variety of treatment options ranging from conservative pain management to endovascular or open surgical extraction of the migrating struts have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of complications could be either during its insertion, e.g. penetration of the IVC) [13] , penetration to the aortic lumen or vertebral body [14] , or occlusion after insertion by filter thrombus [12] , migration of the filter in a whole [15][16][17][18][19][20][21] or in part in the form an embolus of fractured part [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Even rupture of the tricuspid valve [17] , rupture of the free wall of the right ventricle [18] , and cardiac tamponade [19] , that might cause sudden death [20] . Also, migration to the pulmonary artery [21] , fracture and embolization leading to cardiac tamponade had been documented [22] . Moreover, tilting of the filter was also reported [23] .…”
Section: Introductionmentioning
confidence: 99%